Self Efficacy and Work Life Balance On Job Satisfaction - Salsabilla, Amalia; Chichi Andriani (Human Resource Management Studies, 2023)
This study aims to analyze effect self-efficacy and work-life balance at PT. Bank Nagari Branch Pariaman and job satisfaction. This study's population consisted of 49 employees. Total sampling is utilised with a sample size of 49 employees. The instrument for research was a questionnaire. The results of the SPSS Version 26 test indicate that self-efficacy and work life balance both have positive and significant effects on job satisfaction.